Προσεγγίσεις επιλογής συστημάτων χειρισμού εμπορευματοκιβωτιών σε λιμενικούς σταθμούς διακίνησης εμπορευματοκιβωτίων: εφαρμογή στο λιμάνι της Θεσσαλονικής - Παπαδόπολης-Δετζώρτζης, Αριστοτέλης-Νικόλαος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Πολιτικών Μηχανικών, 2018)
The present Dissertation Thesis aims to analytically describe the available equipment in the international market, for handling container boxes (Twenty Feet Equivalent Unit or Forty Feet Equivalent Unit) at a seaside container terminal. In addition, an initial approach is attempted in the procedure of selecting the suitable system of container -box handling equipment in a container terminal, based on the size of the berthing vessels and the estimated annual volume of container boxes. The procedure of designing a container terminal and the selection of the suitable equipment is a dynamic process, which can and should be modified in order to achieve increased container terminal productivity, especially in a field related to the very competitive area of international shipping. It is important to begin by giving some basic definitions : Seaside container terminal is a port or a terminal in which almost exclusively container ships are being served. The specialized equipment used for handling the container boxes at a container terminal is called Container Handling Equipment. Containers boxes are steel boxes with dimensions according to certain international standards, and high resistance to mechanical stresses induced during a sea journey. The boxes are loaded with dry or liquid commodities transported all over the world. During the recent years waterborne transport presents a significant increase, which is due to improvement on the standard of living conditions on a global scale and the decrease on the sea- transportation cost, mainly due to the use of container boxes. Contemporary container ships are classified in various ways, one of which is the one described below: • Panamax and small size container ships used on a local scale called feeders • Post Panamax and Super Post Panamax container ships • New Panamax container ships • Post New Panamax container ships • Triple E class and Giga class container ships. The most important issue in the design process of a container terminal and in the process of selecting the proper container-box handling system is the design vessel (maximum and average) and the estimated annually transported container volume (i.e. number of container-boxes). Due to major increase in the size of new container ships, it is not feasible, for technical and but also for reasons of economy, for large container ships to berth in all ports. For this reason certain basic ship-routes have been formed by the so-called mainliner services, which are followed by the mega container ships (called mother ships), whilst the distribution on a local level is achieved using smaller container ships called feeders. Thus the essential criterion in the design of a container terminal is whether it will accommodate mega container ships (mother ships) or smaller feeder container ships (feeders) or both. It is easily understood that ports serving mainliner container vessels have considerable advantage. Besides the above, the following information should be taken into account during the design procedure : • Main & feeder lines in the area • Imports, Exports , trans-shipment traffic and transit traffic, serviced by rail or road transport • Loaded or Empty container boxes • Containers Size distribution between Twenty or Forty Feet Equivalent Unit (T.E.U.) or (F.E.U.) • Full Container Load (F.C.L.) or Less than Container Load (L.C.L.) container boxes. The container terminal is divided in two basic zones, the seaside operations zone and the landside operations zone. The sea zone is divided in three areas: • Anchoring area • Approach channel area • Berthing area. The land zone is divided in three areas: • Quay wall area • Stacking area • Land delivery/receipt area. The specialized equipment used in a container terminal for: • Loading and unloading of container ships (Ship To Shore) • Horizontal transportation of the boxes from quay wall area to the stacking yard and vice versa • Stacking the container boxes in stacking yard area • Horizontal transportation of the boxes from the stacking yard area to the landside operations area • Loading and unloading trucks and trains on the landside operations (receipt/delivery) area is the Container Handling System of the Container Terminal. The equipment of the Container Handling System is divided into two main categories: (a) Cranes or Gantry Cranes on Quay side or Loading and Unloading Cranes or Ship To Shore (STS) Cranes. The most important equipment of a container terminal is the Ship To Shore or Quay Gantry Cranes. They represent the equipment that determines the size of the maximum vessel that can be served on the terminal, as well as the loading / unloading rate (TEU per hour). Besides the Quay Gantry Cranes (QGC) there are other types of smaller cranes that are analytically described in the chapters following. (b) Vehicles for intra-terminal horizontal transportation and stacking cranes. A wide variety of systems / equipment is available, in the international market, for horizontal transportation and stacking in various stacking heights. The Container Handling Systems are divided in groups, detailed in subsequent sections, as shown in Drawing 33 (Εικόνα 33). For the intra-terminal horizontal transportation the following equipment alternatives can be used:  Tractor – Trailer Units of various types. The trailer can be one suitable for port use only or for street use, single or multiple trailers. (passive vehicle)  Forklift truck (non-passive vehicle)  Reach Stacker (non-passive vehicle)  Straddle Carrier (SC) or Shuttle Carriers (ShC) (non-passive vehicle)  Automated Guided Vehicle (passive vehicle) The intra-terminal horizontal transport vehicles are divided into two categories: (a) passive vehicles and (b) non-passive vehicles. The passive vehicles need assistance from another vehicle / crane for their loading / unloading, whilst the non-passive complete (even at low rate sometimes) both horizontal transportation and loading / unloading procedure themselves without assistance from another vehicle / crane. For stacking the following equipment can be used:  Forklift truck (non-passive vehicle)  Reach Stacker (non-passive vehicle)  Straddle Carrier (SC) or Shuttle Carriers (ShC) (non-passive vehicle)  Ruber Tyred Gantry Crane (RTGC )  Rail Mounted Gantry Crane (RΜGC )  Over Head Crane (OHC) on concrete or steel frames Two basic systems of inter-terminal transportation and stacking can be distinguished:  Systems with common equipment for inter-terminal transportation and stacking (Tractor – Trailer Unit, Forklift, Reach-stacker, Straddle Carriers)  Systems with different equipment inter-terminal transportation and stacking. The most commonly used are the Straddle Carriers, Rubber Tyred Gantry Cranes, Rail Mounted Gantry Cranes. For the evaluation of the productivity and the effectiveness of a container terminal, the following Key Performance Indicators should be counted: • Waiting time of a ship at anchor • Time of a ship on quay • Number of container moves per STS in a certain period of time • Traffic & Throughput indicators For the evaluation of the Container Handling System in the case of high stacking the following should be taken into account: • Acquisition / procurement cost and operation cost • Compatibility with labor standards • Flexibility / layout modification • Response to peak demands • Delays response / interaction